BAHASA SMS DARI SEGI GRAFOLOGIS, SINTAKSIS, DAN PSIKOLINGUISTIK SERTA IMPLIKASINYA TERHADAP PEMBELAJARAN BAHASA INDONESIA - Morelent, Yetty (AT-TALIM, 2013)
Â The high frequency use of phone- cell and short message service has produced various forms of new words.Â  These words create such variation of language that needs to be interpreted.Â  This is so because the results of abbreviations tend to go beyond grafology, syntax, and may produce psycholinguistic impacts.Â  The fact that the creativity of the language users are very expressive and subjective it frequently breaks the linguistic aspects.Â  These inappropriate words which is caused by irregular abbreviation seems so serious that writingÂ  instruction of Indonesian at school must be reconsidered.Â  The phenomenon suggests that one can easily find studentsâ writing which are not understood, there have been so many illogical sentences, and ineffective language.Â  Therefore, school teachers have to work hard to rearrange studentsâ activity so that their writing skills may achieve the appropriate level based on the patterns of effective sentences.CopyrightÂ Â©Â 2013 by Al-TalimÂ AllÂ rightÂ reservedDOI:Â 10.15548/jt.v20i3.45